2019
DOI: 10.1016/j.adolescence.2019.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Moderating effect of trait emotional intelligence on the relationship between parental nurturance and prosocial behaviour

Abstract: Introduction: Research on the moderating role of trait emotional intelligence (EI) has typically examined this construct in light of other risk factors and their detrimental effects on adolescents' outcomes. This study aims to expand this line of research by focusing on the enhancing effect of trait EI and its moderating effects on the relationship between parental nurturance and adolescents' prosocial behaviour. According to such view, higher trait EI was expected to enhance the positive effect of parental nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 42 publications
1
8
0
1
Order By: Relevance
“…More specifically, Ruvalcaba-Romero, Gallegos-Guajardo and Fuerte [44] showed that social-emotional competencies such as adaptability or interpersonal competence predict the appearance of prosocial behaviours. Likewise, not only is emotional intelligence related to these behaviours, but they also influence positive family experiences, determining their future development [64]. In this way, the results of this study can be explained by the fact that emotional and social skills allow us to understand and control our own emotions, to be aware of other people's needs and to maintain positive relationships, so that the development of prosocial behaviour is made possible [65].…”
Section: Discussionmentioning
confidence: 77%
“…More specifically, Ruvalcaba-Romero, Gallegos-Guajardo and Fuerte [44] showed that social-emotional competencies such as adaptability or interpersonal competence predict the appearance of prosocial behaviours. Likewise, not only is emotional intelligence related to these behaviours, but they also influence positive family experiences, determining their future development [64]. In this way, the results of this study can be explained by the fact that emotional and social skills allow us to understand and control our own emotions, to be aware of other people's needs and to maintain positive relationships, so that the development of prosocial behaviour is made possible [65].…”
Section: Discussionmentioning
confidence: 77%
“…Los estudios recientes dan continuidad al análisis del rol mediador de los factores emocionales en la relación entre la crianza y las conductas prosociales (Batool & Lewis, 2020;Davis & Carlo, 2018;Gallitto & Leth-Steensen, 2019;Syahril et al, 2020;Llorca et al, 2017;Taylor et al, 2013) y sus hallazgos dan mayor soporte empírico en cuanto al papel mediador que tienen la empatía, la inteligencia y regulación emocional en la asociación entre los estilos de crianza, la disciplina y prácticas de socialización parental y los comportamientos prosociales de hijos e hijas. Adicional a esto, se evidencia un giro importante en la evolución de la investigación psicológica en tanto se generó un interés por los factores interculturales asociados a la crianza y el desarrollo prosocial (Davis et al, 2015;Davis et al, 2017;Gryczkowski et al, 2017;Knight et al 2015;Knight et al, 2016;Maiya et al, 2020).…”
Section: Estudios Recientes (Hojas)unclassified
“…One of the variables with the greatest structural weight in predicting PB in any population group is emotional intelligence (EI) [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. Studies of EI support the role of cognitive, affective–emotional, and motivational modulators in PB that, when linked to balanced emotional programs, can allow forms of interpersonal social interaction that enhance well-being and life satisfaction.…”
Section: Introductionmentioning
confidence: 99%